Soldier Health and Position Tracking System - Dr. Basavaraj G Kudamble,; G Naveena,; G Naveena,; L Vidya,; K Vijay,; C Manoj,; T Venkata Prasad, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The Soldier Health and Position Tracking System (SHRYS) is an integrated technological solution designed to address the multifaceted challenges associated with monitoring and ensuring the well-being of military personnel in dynamic and unpredictable operational environments. This system amalgamates state-of-the-art wearable devices, GPS technology, and health monitoring sensors to provide comprehensive real-time insights into soldiers' physical conditions and locations. The wearable devices continuously collect vital health metrics such as heart rate, body temperature, and activity levels, fostering a proactive approach to healthcare management. Simultaneously, the GPS technology enables precise and continuous tracking of soldiers' positions on the battlefield. The collected data is then transmitted to a centralized monitoring system, where advanced analytics and machine learning algorithms assess soldiers' health trends, detect anomalies, and facilitate timely medical interventions. The SHPTS aims to enhance the overall situational awareness of military commanders, optimize resource allocation, and ultimately ensure the optimal health and safety of soldiers deployed in challenging and high-risk scenarios. This innovative system stands at the forefront of leveraging technology to safeguard the well-being and operational effectiveness of military personnel.
Keywords: Rasberry Pi 4; GPS Module; GSM; LCD; Heartbeat Sensor; Temparature Sensor; Pressure Sensor